The Personality Typology of the Main Character in the Short Story “Syaikh Balbis” by Taufiq al-Hakim (A Literary Psychology Study) - Eka Nadiansyah; Rasyad; Abdul Razak; Nur Chalis; Emi Suhemi (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to analyze the personality types of the main character in the short story Syaikh Balbis by Taufiq al-Hakim. The research employs a descriptive qualitative method using the Hippocrates–Gallenus literary psychology personality type theory as its analytical approach. This study uses written data found in Taufiq al-Hakim’s short story Syaikh Balbis, which demonstrates the compatibility of the main character’s personality type with the Hippocrates–Gallenus perspective. The data collection methods used in this study include reading and note-taking techniques, library research, close reading, and manual coding. The data were analyzed using data analysis techniques consisting of identification, analysis, and conclusion drawing. The findings of this study indicate that four personality types according to Hippocrates—sanguine, choleric, melancholic, and phlegmatic—are present in the characters of Taufiq al-Hakim’s short story Syaikh Balbis. The researcher hopes that this study may serve as a reference for future research related to the Hippocrates–Gallenus literary psychology theory.